Roles of post-transcriptional modifications in Solanum lycopersicum - Grundy, Cameron H S (2022)
Methylation at the N6 position of internal adenosines (m6A) is known as the most prevalent and widespread modification in mRNA. In plants, m6A has roles in post-transcriptional gene control, influencing growth, development and reproduction. The function of these modifications is often mediated by RNA binding proteins containing a YT521-B homology (YTH) domain. These domains contain a hydrophobic pocket that can directly accommodate m6A residues. Despite studies demonstrating that m6A is crucial for plant development and multiple studies on mammalian YTH proteins, very little is known about YTH proteins in plants.